Analytical and clinical comparison of different immunoassay systems for the detection of antiphospholipid antibodies. (5th February 2016) - Montaruli, B.; De Luna, E.; Erroi, L.; Marchese, C.; Mengozzi, G.; Napoli, P.; Nicolo', C.; Romito, A.; Bertero, M. T.; Sivera, P.; Migliardi, M.
Summary: Introduction: We evaluated analytical and clinical performances of IgG and IgM anticardiolipin (aCL) antibodies and anti‐β2‐glycoprotein I (a‐β2GpI) antibodies and upper limit reference ranges (99th percentiles) in comparison with manufacturer's cutoff values with different commercial methods. Methods: We assayed aCL and a‐β2GpI in serum samples from 30 healthy individuals, 77 patients with antiphospholipid syndrome (APS) diagnosed according to the Sydney criteria, 51 patients with autoimmune diseases, eight patients with previous thrombotic events, six patients with other diseases, and 18 patients with infectious diseases, using ELISA Inova Diagnostics; EliA Phadia Laboratory Systems; CliA Zenit‐RA; and CliA Bio‐Flash. Results: Anticardiolipin and a‐β2GpI IgG and IgM immunoassays showed good analytic performances with both 99th percentile and manufacturer's cutoff reference values. Our results showed fair to moderate agreement among assays. In‐house cutoff values gave significantly better performances only for a‐β2GpI IgG with all the immunoassays analyzed with the exception of Inova CliA Bio‐Flash where we obtained the same performances with in‐house and manufacturer's cutoffs. Conclusions: By guidelines, all laboratories are strongly advised to validate/verify the manufacturer's cutoff values. We recommend establishing low‐positive, medium‐/high–positive, and high‐positive CliA IgG aCL and a‐β2GpI ranges in order to help clinicians in the diagnosis and treatment of APS.